The Indirect Impact of Entrepreneurial Gender on Innovation of Enterprises in China - Li, Aijie (Université d'Ottawa / University of Ottawa, 2020)
This research examines the mediation effects of prior experience, access to finance, government regulation, and workforce skills on entrepreneurial gender and corporate innovation in China. The aim is to study the factors that influence innovation decisions of women entrepreneurs and to promote corporate innovation in women-owned enterprises in developing countries like China. The data of this research comes from China Enterprise Survey conducted by World Bank in 2012. The findings revealed that prior experience, government regulation, and workforce skills have significant individual mediation effect on the relationship between entrepreneurial gender and corporate innovation. Also, prior experience, access to finance, government regulation, and workforce skills together played a significant overall mediating effect on corporate innovation in women-owned enterprises. The results of this study will provide important insights to women owners of enterprises, policy makers, and researchers to further understand the influence of prior experience, access to finance, government regulations, and workforce skills on corporate innovation in China and other emerging countries.
Keywords: Entrepreneurial Gender; Innovation; Prior Experience; Access to Finance; Government Regulation; Workforce Skills